Providing Public School Education in Developing Countries: A Theoretical Analysis - Bagala P. Biswal (Queen's University, Department of Economics, 1993)
Provision of universal free public education has been argued for in the literature on equity ground. This paper develops a new model of public school education and demonstrates how the presence of private tutoring in developing countries, compromises the above argument. The teachers, by shirking at school and supplying private tutoring to the students at a cost, divert the benefits of free public education towards themselves. This model also conforms with the merit-cum-means principle adopted in developing countries to subsidize the education of the poor and high ability students when it is extended to an heterogeneous environment.
Keywords: H42; H52; I22; 330; private tutoring; club; imperfect monitoring